PELAKSANAAN MANAJEMEN POSKESTREN DI PONDOK PESANTREN DARUL FUNUN EL-ABBASIYAH PADANG JAPANG - Nasrullah Nasrullah (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This reseach was focused on the implementation of management function in Darul Funun El-Abbasiyah Padang Japang’s Boarding School. This reseach used qualitative approach by conducting observation, interview, and documatation study. The school generally had done the function of management by applying planning, organizing, actuating and controlling function. The success was signed when this school could improve the health services, health living and environmental health.Keywords: Management, Boarding School, Darul Funun El-Abbasiyah